ABSORPTION OF NEEM (Azadirachta indica) SEED OIL BY SPLIT-BAMBOO (Bambusa vulgaris) AT DIFFERENT TEMPERATURE REGIMES AND TREATMENT DURATIONS - Erakhrumen, Andrew Agbontalor (Floresta, 2012)
This study was carried out to evaluate absorption of neem (Azadirachta indica A. Juss) seed oil by split-bamboo (Bambusa vulgaris Schrad. ex J.C. Wendl.) samples at two different treatment temperature (TT) regimes and durations of treatment (DOT). A multivariate linear regression model was also developed for predicting oil absorption (OA) from TT and DOT. Split-bamboo specimens from the same source with same dimension were oven-dried at 103 ± 2 oC, conditioned to 11.76% mean moisture content, and treated by completely soaking a set in oil at an ambient room temperature of 25 ± 2 oC for 24 hours (A) and by soaking the other in hot oil at 60 oC for 4 hours (B). Results obtained showed that test specimens for A and B had mean OA values of 57.02 ± 3.23 and 124.30 ± 7.26 kgm-3 respectively. Regression model developed for predicting OA from TT and DOT had a coefficient of determination of 0.93 with a significant ANOVA result (p < 0.05). Implications of the results obtained were discussed while conclusions and recommendations were made in line with the outcome of the study. Keywords: Lignocellulosic materials; vegetable oil; preservative properties; test variables; non-pressure treatment. Resumo Absorção de óleo de sementes de nim (Azadirachta indica) por bambu fracionado (Bambusa vulgaris) em diferentes temperaturas e durações de tratamento. Este estudo foi realizado para avaliar a absorção de óleo de sementes de nim (Azadirachta indica A. Juss) por bambu fracionado (Bambusa vulgaris Schrad. Ex JC Wendl.) com amostras em duas temperaturas (TT) e diferentes durações do tratamento (DOT). Um modelo de regressão linear múltipla foi também desenvolvido para predizer a absorção de óleo (OA) de TT e DOT. Espécimes de bambu picado provenientes da mesma fonte com mesma dimensão foram secas em estufa a 103 ± 2 ºC, condicionados a 11,76% de teor médio de umidade e tratados por imersão em óleo a uma temperatura ambiente de 25 ± 2 ºC por 24 horas (A), embebendo-se o outro em óleo quente a 60 ºC durante 4 horas (B). Os resultados obtidos mostraram que as amostras de teste para A e B tinham valores médios de 57,02 OA ± 3,23 e 124,30 ± 7,26 kg.m-3, respectivamente. O modelo de regressão desenvolvido para predizer a OA de TT e DOT teve um coeficiente de determinação de 0,93, com um resultado da ANOVA significativo (p <0,05). Implicações dos resultados obtidos foram discutidos enquanto conclusões e recomendações foram feitas de acordo com o resultado do estudo. Palavras-chave: Materiais lignocelulósicos; óleo vegetal; propriedades conservantes; variáveis de teste.